Non-proteasomal UbL-UbA family of proteins in neurodegeneration - Salinee Jantrapirom (2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. Ubiquitin-like/ubiquitin-associated proteins (UbL-UbA) are a well-studied family of non-proteasomal ubiquitin receptors that are evolutionarily conserved across species. Members of this non-homogenous family facilitate and support proteasomal activity by promoting different effects on proteostasis but exhibit diverse extra-proteasomal activities. Dysfunctional UbL-UbA proteins render cells, particularly neurons, more susceptible to stressors or aging and may cause earlier neurodegeneration. In this review, we summarized the properties and functions of UbL-UbA family members identified to date, with an emphasis on new findings obtained using Drosophila models showing a direct or indirect role in some neurodegenerative diseases.